The Impact of Performance Supplements on Irritable Bowel Syndrome-like Gastrointestinal Distress in Athletes - Utnik, Martyna; Bajur, Patrycja; Czereczon, Wiktor; Działowy, Maksymilian; Uszko, Milena (Quality in Sport, 2026)
Background. Athletes frequently experience gastrointestinal (GI) disturbances overlapping with Irritable Bowel Syndrome (IBS). Performance supplements—including carbohydrate gels and beverages, protein powders, creatine, caffeine-based pre-workouts, probiotics, prebiotics, and buffering agents—can mechanistically exacerbate or attenuate these symptoms. Aim. To summarize human data (2021–2026) regarding the effects of performance and recovery supplements on IBS-like symptoms in athletes, identifying mechanistic themes and research gaps. Material and methods. This narrative review synthesized evidence from PubMed and Scopus, including observational studies and clinical trials. Results. No identified trials recruited athletes with Rome-defined IBS, though a high prevalence of IBS-like symptoms was documented. Multi-strain Lactobacillus or Bifidobacterium probiotics showed small-to-moderate reductions in symptom severity in several randomized trials. Conversely, prebiotics and high-FODMAP (Fermentable Oligosaccharides, Disaccharides, Monosaccharides, and Polyols) sports products were linked to increased lower-GI burden. Experimental data indicated higher symptom rates with solid carbohydrates compared to gels or beverages at equivalent dosages. Sodium bicarbonate remains strongly associated with GI discomfort, despite novel hydrogel delivery systems. Emerging "gut-supportive" supplements (e.g., collagen peptides, multi-ingredient fermented whey) showed neutral acute effects or preliminary, uncontrolled chronic improvements. Conclusions. Supplement effects are highly dependent on FODMAP content, osmolality, and underlying GI vulnerability. Multi-strain probiotics and low-FODMAP carbohydrate strategies demonstrate the most consistent potential for symptom reduction. High-priority research should focus on rigorously phenotyped athletes with confirmed IBS and head-to-head trials of low- vs. high-FODMAP formulations.